2023
DOI: 10.3390/pathophysiology30020020
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors and Clinical Characteristics of Acute Kidney Injury in Patients with COVID-19: A Systematic Review and Meta-Analysis

Abstract: Acute kidney injury (AKI) is associated with a worse prognosis in coronavirus disease 2019 (COVID-19) patients. Identification of AKI, particularly in COVID-19 patients, is important for improving patients’ management. The study aims to assess risk factors and comorbidities of AKI in COVID-19 patients. We systematically searched PubMed and DOAJ databases for relevant studies involving confirmed COVID-19 patients with data on risk factors and comorbidities of AKI. The risk factors and comorbidities were compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 72 publications
(127 reference statements)
1
6
0
Order By: Relevance
“…The median age of patients diagnosed with AKI was 65 years. Furthermore, studies have shown that the risk of developing acute renal failure is three times higher in patients aged >65 years than in younger patients [ 28 ]. Increased age has been reported as a risk factor in AKI patients because of the physiological and structural changes in the kidneys with aging, which reduce nephron mass and glomerular filtration rate with an increased tendency towards cellular apoptosis [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The median age of patients diagnosed with AKI was 65 years. Furthermore, studies have shown that the risk of developing acute renal failure is three times higher in patients aged >65 years than in younger patients [ 28 ]. Increased age has been reported as a risk factor in AKI patients because of the physiological and structural changes in the kidneys with aging, which reduce nephron mass and glomerular filtration rate with an increased tendency towards cellular apoptosis [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…In females, during the menstrual cycle, estrogen acts as a protective and therapeutic agent for the kidneys; however, this short-term effect decreases with age [ 29 ]. Furthermore, in a recent Systematic Review and Meta-Analysis, male gender was one of the many risk factors that placed COVID-19 patients at greater risk of developing AKI (OR: 1.74 (1.47, 2.05), P < 0.05) [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Apart from AKI, a substantial percentage of patients develops proteinuria during SARS-CoV-2 infection [ 113 ]. There are several potential reasons for this, some due to a possible direct pathogenetic effect of the virus in the kidney and others due to the systemic effects of the infection and critical illness.…”
Section: Long Covid and Implication For Cardiovascular Diseasementioning
confidence: 99%
“…Advanced age, the presence of diabetes and obesity, cardiovascular disease, persistent CKD, acute respiratory distress syndrome and mechanical ventilation, nephrotoxic drugs, and hypotension with tissue hypoxia and vasopressor recruitment are several risk factors for the development of AKI in COVID 19 patients [37].…”
Section: Acute Kidney Injury (Aki) Associated With Covid-19mentioning
confidence: 99%